2015
DOI: 10.1097/ipc.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Central Line–Associated Bacteremia After the Introduction of Midline Catheters in a Ventilator Unit Population

Abstract: HypothesisOur objective was to evaluate whether the use of midline venous catheters in place of central line venous catheters, when appropriate, decreased the overall incidence of central line–associated bacteremia in a ventilator unit.MethodsThe time interval between February 2012 and February 2013 was divided into 2 periods. Group A was the first half of the year, before the introduction of midline catheters, and group B was the second half of the year, 6 months after their introduction. Central line–associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
0
31
0
2
Order By: Relevance
“…7,12 While there is a paucity of information that directly compares PICCs to midlines, some data suggest a lower risk of bloodstream infection and thrombosis associated with the latter. [24][25][26] For example, at one quaternary teaching hospital, house staff who are trained to insert midline catheters under ultrasound guidance in critically ill patients with difficult venous access reported no CLABSI and DVT events. 26 Interestingly, multilumen catheters were used twice as often as single lumen catheters in patients with short-term PICCs.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 While there is a paucity of information that directly compares PICCs to midlines, some data suggest a lower risk of bloodstream infection and thrombosis associated with the latter. [24][25][26] For example, at one quaternary teaching hospital, house staff who are trained to insert midline catheters under ultrasound guidance in critically ill patients with difficult venous access reported no CLABSI and DVT events. 26 Interestingly, multilumen catheters were used twice as often as single lumen catheters in patients with short-term PICCs.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 13 Another study recently demonstrated a decrease in the rate of CLABSI by introducing a midline program in a ventilator unit. 12 …”
Section: Introductionmentioning
confidence: 99%
“…10 Midline catheters with lengths of 6 to 20 cm are a potential solution and have high success rates and longevity, but inserters require specialized training, the costs are significantly higher, and the rate of complications including thrombosis and infection appears far higher. [11][12][13][14][15][16][17][18][19] The recent introduction of 6.35-cm ultralong peripheral intravenous lines may provide the benefits of midline catheters without the costs and complications. We hypothesized that ultralong catheters would have improved survival and a similar safety profile compared with the standard 4.78-cm intravenous catheter.…”
Section: How This Is Relevant To Clinical Practicementioning
confidence: 99%